Speech act of concern on the academic performance of Malaysian foster children - How, Cherish; Jariah Mohd Jan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Language is vital in expressing concern as it allows one to explain their feelings, ideas and behaviour. Teachers and caregivers are concerned about the poor academic performance of foster children as these children have low grades on tests and high dropout rates. Those with poor academic performance might be vulnerable to secure a better life when they leave home. Nevertheless, studies on concern in regards to Malaysian foster children’s academic issues from a language perspective are scarce. Hence, this qualitative study uses speech act categories and stages of concern to examine the voices of concern, of teachers and caregivers towards the academic performance of foster children. The data were collected from semistructured interview sessions with teachers and caregivers. Findings reveal that teachers and caregivers are highly concerned about the poor academic performance of foster children as their responses are most prominent in the stage of refocusing. They attempted to reach out to address foster children’s academic needs by giving suggestions. However, they face challenges in addressing these children’s academic needs and issues. Representative act is highly utilised by teachers and caregivers to describe, report or explain about problems in trying to help the children. This study contributes to the area of speech acts on concern especially on the academic performance of foster children in Malaysia.